Legal Framework for Municipal Waste Landfills in the European Union - Bugarski, Tatjana; Tubic, Bojan; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Inadequate disposal of waste in landfills produces harmful effects on the environment and human health. In order to prevent or reduce them to a minimum, states devise alternative approaches to waste management and / or prescribe technical requirements for landfilling. In the European Union the Landfill Directive has been adopted, which aims to ensure the gradual reduction of amount of waste disposed in landfills, especially those suitable for recycling or other disposal operations, as well as to provide for measures, procedures and guidelines to prevent or minimize the adverse effects of landfills on the environment, by stipulating strict operational and technical requirements for waste and landfills. The subject of this paper is the analysis of the content of the Directive and its application, with special reference to the case law of the Court of Justice of the European Union in proceedings against Member States that have not complied with the obligations set out in this Directive.